The Forward Model: A Unifying Theory for the Role of the Cerebellum in Motor Control and Sense of Agency - Welniarz, Quentin; Worbe, Yulia; Gallea, Cecile (Frontiers in Systems Neuroscience, 2021)
For more than two decades, there has been converging evidence for an essential role of the cerebellum in non-motor functions. The cerebellum is not only important in learning and sensorimotor processes, some growing evidences show its implication in conditional learning and reward. More recent work has demonstrated that the cerebellum is also required for the sense of agency, a cognitive process that allows considering an action as our own, suggesting that cerebellum may serve as an interface between sensorimotor function and cognition. A unifying model that would explain the role of the cerebellum across these processes has not been fully established. Nonetheless, an important heritage was given by the field of motor control: the forward model theory. This theory stipulates that behaviours are controlled based on the constant interactions between our organism and its environment through feedforward and feedback loops. Feedforward loops predict what is going to happen, while feedback loops confront the prediction with what happened so that we can react accordingly. From an anatomical point of view, the cerebellum is at an ideal location at the interface between the motor and sensory systems, as it is connected to cerebral, striatal and spinal entities via parallel loops, so that it can link sensory and motor systems with cognitive processes. Recent findings that the cerebellum participates in building the sense of agency as a predictive and comparator system will be reviewed together with a past work on motor control within the context of the forward model theory.